Patient safety awareness and attitude among interns of a tertiary care hospital - Ayesha Abubakar Mitha; Mahboob, Usman (Journal of the Pakistan Medical Association, 2021)
Background: Patient Safety (PS) emerging as global health problem. PS attitudes are being assessed worldwide but behaviors and attitudes in young doctors have not been studied in great depth. Aim: To assess knowledge and attitude towards PS in Foundation Year Trainees (Interns) in a tertiary care hospital. Method: A cross sectional Survey was applied to 126 Interns of Combined Military Hospital Lahore using Questionnaire (APSQ) in December 2019. The survey was kept anonymous. Statistical analysis was by utilizing SPSS Version 23. Results: Interns had PS knowledge. Highest domain score was “Attitude to medical error reporting” (53.34 + 7.62) followed by “PS knowledge” (50.88 + 6.85). The lowest domain score was “Attitude to PS Skills” (16.34 + 3.46). Pearson correlations revealed significant correlation between domains. Conclusion: The study showed that there was prevalence of PS knowledge among interns but limited understanding requiring training. KEYWORDS: Attitude, patient safety, medical errors, interns Continuous...